Transmission of an inhomogeneous state via resonant tunnelling - Saffin, Paul M.; Padilla, Antonio; Copeland, Edmund J. (Springer, 2008)
We recently investigated the nature of resonant tunnelling in standard scalar Quantum Field Theory, uncovering the conditions required for resonance. It was shown that whereas the homogeneous false vacuum may decay via bubble nucleation, it may not decay in a resonant fashion. The no-go theorem given there is circumvented in this study by considering an initial state other than the homogeneous false vacuum, and we confirm our mechanism by showing in an explicit model how resonant tunnelling occurs. Using this model we demonstrate how the tunnelling rate depends on the energy of specially constructed initial states, with these states corresponding to contracting spherical bubbles of some vacuum that evolve to a minimum radius and then tunnel to another vacuum, instead of the classical motion where the bubble would just start to expand.